2020
DOI: 10.1038/s41422-020-0349-y
|View full text |Cite|
|
Sign up to set email alerts
|

863 genomes reveal the origin and domestication of chicken

Abstract: Despite the substantial role that chickens have played in human societies across the world, both the geographic and temporal origins of their domestication remain controversial. To address this issue, we analyzed 863 genomes from a worldwide sampling of chickens and representatives of all four species of wild jungle fowl and each of the five subspecies of red jungle fowl (RJF). Our study suggests that domestic chickens were initially derived from the RJF subspecies Gallus gallus spadiceus whose present-day dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
226
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 181 publications
(260 citation statements)
references
References 84 publications
14
226
1
1
Order By: Relevance
“…They possess their own genetic structure in subgroups. In admixture result, game breeds and red jungle clustered as one group until K = 16, suggesting domestic breeds and wild populations have mutual introgression (Li et al, 2019;Wang et al, 2020). It is consistent with our NJ tree results that all breeds from the same population clustered, except that game breeds.…”
Section: Discussion Population Structure and Genetic Diversitysupporting
confidence: 88%
See 2 more Smart Citations
“…They possess their own genetic structure in subgroups. In admixture result, game breeds and red jungle clustered as one group until K = 16, suggesting domestic breeds and wild populations have mutual introgression (Li et al, 2019;Wang et al, 2020). It is consistent with our NJ tree results that all breeds from the same population clustered, except that game breeds.…”
Section: Discussion Population Structure and Genetic Diversitysupporting
confidence: 88%
“…Red junglefowl, which is considered to be the ancestor of the domesticated chicken (Murray, 2016;Wang et al, 2020), showed no significant difference in the heterozygosity diversity between the Chinese local chicken breeds in our study. Malomane et al (2019) has reported similar observed heterozygosity in RJF compared with that of our study.…”
Section: Discussion Population Structure and Genetic Diversitycontrasting
confidence: 60%
See 1 more Smart Citation
“…The world-wide distribution of chicken is a fascinating example of a successful story of crossspecies relationship with human. Although chicken domestication has been a controversial topic for decades, a recent study published in Cell Research by Wang and colleagues (2020) seems to have taken the field a step forward in answering key questions on the geographic and temporal origins of chicken domestication [302]. Erasmus, Darwin's grandfather, was one of the first to suggest that the red junglefowl (Gallus gallus) was the wild ancestor of the domestic chicken.…”
Section: It All Began In the Wild Asian Forestsmentioning
confidence: 99%
“…However, with the advent of SNP arrays and next-generation sequencing technologies, chicken domestication was proposed to have occurred via multiple independent events in different areas of Asia between 7,000 and 10,000 AC [189,158] from at least two wild progenitors [94]. The 'multiple origins' hypothesis has recently been questioned by Wang et al (2020). In their study on 863 chicken genomes from a variety of domestic breeds and wild (sub)species, the authors showed that domestic chickens were initially derived from the wild red junglefowl subspecies G.g.…”
Section: It All Began In the Wild Asian Forestsmentioning
confidence: 99%